2017
DOI: 10.1119/1.5003738
|View full text |Cite
|
Sign up to set email alerts
|

Making Visual Illustrations of Physics Accessible to Blind Students

Abstract: The teaching of physics often involves the use of illustrations that complement and assist the understanding of a particular situation or physical phenomenon. Overall, the proper use of illustrations can maximize the learning and understanding of concepts and phenomena related to the teaching of science (physics, chemistry, biology) and mathematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Recent research has begun to investigate the accessibility of physics departments [46] and curriculum [3], and multiple studies have problematized and addressed barriers experienced in physics labs for individuals with auditory or visual impairments [47][48][49]. However, little work has investigated the specific experiences of students with nonapparent disabilities in physics courses.…”
Section: Existing Supports For Students With Disabilities Providedmentioning
confidence: 99%
“…Recent research has begun to investigate the accessibility of physics departments [46] and curriculum [3], and multiple studies have problematized and addressed barriers experienced in physics labs for individuals with auditory or visual impairments [47][48][49]. However, little work has investigated the specific experiences of students with nonapparent disabilities in physics courses.…”
Section: Existing Supports For Students With Disabilities Providedmentioning
confidence: 99%
“…Most of the literature about supporting students with disabilities in physics target students with visual impairments (59% of articles we identified; e.g., [6][7][8][9][10] ), physical disabilities (23%; e.g., [11][12][13][14][15] ), and hearing impairments (18%; e.g., [16][17][18][19] ). We did not identify any articles related to supporting students with affective, emotional/behavioral, or mental health impairments.…”
Section: Supporting Students With Disabilities In Postsecondary Stemmentioning
confidence: 99%
“…While there have been studies focusing on how to support students with disabilities in physics (for example, see Refs. [5][6][7][8]), a corpus analysis of Physical Review Physics Education Research found that fewer than 1% of articles referred to any form of disability, which indicates that there may not have historically been much attention given to equitable access in our curriculum development [9].…”
Section: Introductionmentioning
confidence: 99%